تحفظِ ناموسِ رسالت ﷺ قرآنی تعلیمات، احادیثِ نبوی، فقہی آراء اور عصری تناظر کا تحقیقی جائزہ: Protection of the Honor of Prophethood (PBUH): A Research Analysis of Quranic Teachings, Prophetic Traditions, Jurisprudential Opinions, and Contemporary Context - Anjum Riaz; Syed Hayatullah; Fouzia Yaseen (International Research Journal of Arabic and Islamic Studies, 2024)
The protection of the honor of Prophet Muhammad (PBUH) holds a central place in Islamic teachings, emphasizing respect, reverence, and safeguarding his sanctity. This research investigates the concept of protecting the dignity of the Prophet (PBUH) in light of Quranic teachings, Hadith literature, and Islamic jurisprudence. Quranic verses underline the profound respect and reverence due to the Prophet (PBUH), including commands to lower one's voice in his presence and directives for unwavering adherence to his guidance. The Hadith literature strengthens this emphasis by associating love and respect for the Prophet (PBUH) with the essence of faith. The study further examines historical incidents during the Prophet’s (PBUH) time where acts of blasphemy were dealt with firmly, demonstrating the Islamic legal framework's stance on the issue. The opinions of classical jurists and scholars from the early centuries are explored, highlighting their consensus on the severity of blasphemy and its repercussions. The analysis also considers the principle of human dignity in Islam, establishing a balance between protecting freedom of expression and upholding the sanctity of prophethood. Additionally, references to earlier divine laws (Sharā’iʿ Min Qablinā) and contemporary debates on blasphemy laws and human rights provide a holistic view of the subject. This study concludes by offering recommendations for fostering interfaith dialogue, preventing misuse of blasphemy laws, and promoting a peaceful understanding of Islamic principles in a pluralistic world.